Lung metastases at the initial diagnosis of high-grade osteosarcoma: prevalence, risk factors and prognostic factors. A large population-based cohort study - Zhang, Chao; Guo, Xu; Xu, Yao; Han, Xiuxin; Wang, Xin; Wang, Guowen (São Paulo Medical Journal, 2019)
BACKGROUND: Osteosarcoma is the most prevalent malignant bone tumor in children and adolescents. Lung metastases are associated with poor prognosis. OBJECTIVE: The aim here was to explore the prevalence of and risk and prognostic factors for lung metas-tases in high-grade osteosarcoma patients. DESIGN AND SETTING: Retrospective cohort study based on the Surveillance, Epidemiology and End Results (SEER) database in the United States. METHODS: Data on 1,408 high-grade osteosarcoma patients registered in the SEER database between 2010 and 2015 were extracted. From these, all patients with high-grade osteosarcoma and initial lung metastasis were selected for analysis on risk and prognostic factors for lung metastases. Overall survival was estimated. RESULTS: There were 238 patients (16.90%) with lung metastases at diagnosis. Axial location, tu- mor size > 10 cm (odds ratio, OR 3.19; 95% confidence interval, CI: 1.58-6.45), higher N stage (OR 4.84; 95% CI: 1.94‑12.13) and presence of bone metastases (OR 8.73; 95% CI: 4.37-17.48) or brain metastases (OR 25.63; 95% CI: 1.55-422.86) were significantly associated with lung metastases. Younger age and sur-gical treatment (hazard ratio, HR 0.46; 95% CI: 0.30-0.71) favored survival. Median survival was prolonged through primary tumor surgery. CONCLUSIONS: The factors revealed here may guide lung metastasis screening and prophylactic treat-ment for osteosarcoma patients. A primary tumor in an axial location, greater primary tumor size, higher lymph node stage and presence of bone or brain metastases were significantly correlated with lung me-tastases. The elderly group (≥ 60 years) showed significant correlation with poor overall survival. For im-proved survival among high-grade osteosarcoma patients with lung metastases, aggressive surgery on the primary tumor site should be encouraged.